FAKTOR KEBERHASILAN PROGRAM NASIONAL PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI JORONG KOTO JAPANG NAGARI PADANG AIR DINGIN - Ega Oktavia; Nilda Elfemi; Elvawati Elvawati (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
The Pamsimas program is a clean water supply program, especially for people who live in rural and suburban areas, but not all Pamsimas programs are successful or last long, for example in the Nagari Padang Air Cold area which consists of four jorongs but only one Jorong where the Pamsimas program is still good and running smoothly. The purpose of this article is to describe the success factors for the implementation of the Pamsimas program in Jorong Koto Japan, Nagari Padang Air cold. The approach used is a qualitative approach using descriptive research type, data collection techniques used are observation, interviews, and document studies. The technique of selecting informants was purposive sampling with 14 informants. Analysis of the data used starts from data collection, data reduction, drawing conclusions. The research location is in Jorong Koto Japan, because among the Jorong-Jorong in Nagari Padang Air cold, only this Jorong has succeeded in its Pamsimas program. Based on the field, it can be concluded that the success factors in implementing the Pamsimas program 1. Ideas or thoughts, such as selecting water sources, how to manage Pamsimas, 2. There is a donation of funds, 3. There is a contribution of personnel, 4. Payment of monthly dues on time, such as monthly payment for clean water.